Magmatic evidence for carbonate metasomatism in the lithospheric mantle underneath the Ohře (Eger) Rift - Brandl, Philipp; Genske, Felix; Beier, Christoph; Haase, Karsten; Sprung, Peter; Krumm, Stefan (Journal of Petrology, 2015)
Magmas erupted in intracontinental rifts typically form from melting of variable proportions of asthenospheric or lithospheric mantle sources and ascend through thick continental lithosphere. This ascent of magma is accompanied by differentiation and assimilation processes. Understanding the composition of rift-related intracontinental volcanism is important, particularly in densely populated active rift zones such as the Ohře (Eger) Rift in Central Europe. We have sampled and analysed nephelinites from Železná hůrka (Eisenbühl), the youngest (<300 ka) Quaternary volcano related to the Ohře Rift where frequent earthquake swarms indicate continuing magmatic activity in the crust. This nephelinite volcano is part of a larger eruptive centre (Mỳtina Maar) representing a single locality of recurrent volcanism in the Ohře Rift. We present a detailed petrographic, mineralogical and geochemical study (major and trace elements and Sr-Nd-Hf-O isotopes) of Železná hůrka to further resolve the magmatic history and mantle source of the erupted melt. We find evidence for a highly complex evolution of the nephelinitic melts during their ascent to the surface. Most importantly, mixing of melts derived from different sources and of strong chemical contrast controls the composition of the erupted volcanic products. These diverse parental melts originate from a highly metasomatized subcontinental lithospheric mantle (SCLM) source. We use a combined approach based on mineral, glass and whole-rock compositions to show that the mantle underneath the western Ohře Rift is metasomatized dominantly by carbonatitic melts. The nephelinites of Železná hůrka formed by interaction between a carbonatitic melt and residual mantle peridotite, partial crystallization in the lithospheric mantle and minor assimilation of upper continental crust. Thermobarometric estimates indicate that the stagnation levels of the youngest volcanism in this part of the Ohře Rift were deeper than the focal depths of recent earthquake swarms, indicating that those are not directly linked to magma ascent. Furthermore, close mineralogical and geochemical similarities between the Železná hůrka nephelinite and fresh kimberlites may point towards a genetic link between kimberlites, melilitites and nephelinites.
Keywords: Assimilation; Carbonated peridotite; Continental rift; Mantle metasomatism; Nephelinite